Anti - aging 7 secrets of holistic health - Zainah Mokhtar (Institut Terjemahan & Buku Malaysia, 2016)
Do you want to remain young? Do you want to be healthy and physically attractive? Do you want to always be dynamic and carry out a variety of tasks with full dedication and motivation? I am sure almost everyone would give the same answer : a resounding "Of course!" If however, the question is slightly altered and it was asked : are you ready to put everything into looking young, and becoming more healthy and energetic? Most of us would probably say : " We'll see...."